STUDI IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERKOTAAN DI KELURAHAN WINONG KECAMATAN BOYOLALI KABUPATEN BOYOLALI - Taufik Agustian; Nina Widowati; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
This research is a qualitative research motivated by the National Program for Urban Community Empowerment (PNPM Mandiri Perkotaan) that still experience difficulties to reducing poverty in Indonesia. The research is focused on the implementation of PNPM Mandiri Perkotaan in Winong, Boyolali and it is influencing factors covering communication, resources, implementor dispotition, bureaucratic structure, implementing organizations, and socio-economic environment.The results showed that the PNPM Mandiri Perkotaan in Winong, Boyolali still less effective and also less positive impact on the development of community life caused by low levels of human resource and poor socialization. So it takes a strategy to improve the quality of human resources as well as good communication strategy in order to improve the welfare of the people in Winong.